2010
DOI: 10.1097/qai.0b013e3181fbcb04
|View full text |Cite
|
Sign up to set email alerts
|

A Way Forward: The National HIV/AIDS Strategy and Reducing HIV Incidence in the United States

Abstract: In July 2010, the Obama Administration released a National HIV/AIDS Strategy for the United States to refocus national attention on responding to the domestic HIV epidemic. The goals of the strategy are to reduce HIV incidence; to increase access to care and optimize health outcomes among people living with HIV; and to reduce HIV-related disparities. The strategy identifies a small number of action steps that will align efforts across federal, state, local, and tribal levels of government, and maximally impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 15 publications
1
63
0
Order By: Relevance
“…In this study, the results showed the prevalence of HIV among Pacific islanders diagnosed with HIV ranges from 1% to 14%. This prevalence is very low as compared with what is observed among MSM [16] but is considered high as it is indicates suboptimum access to health care [17]. However, this is consistent with a study done in Iran (7.14 to 15.95%) in 2010 and South Africa (12.2%) in 2012 [11] [18].…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the results showed the prevalence of HIV among Pacific islanders diagnosed with HIV ranges from 1% to 14%. This prevalence is very low as compared with what is observed among MSM [16] but is considered high as it is indicates suboptimum access to health care [17]. However, this is consistent with a study done in Iran (7.14 to 15.95%) in 2010 and South Africa (12.2%) in 2012 [11] [18].…”
Section: Discussionsupporting
confidence: 66%
“…Hardships are social issues that impact HIV and require public health scientists to broaden their current focus on surveillance and behavior modification to include policy interventions aimed at reducing social inequities that contribute to the production of HIV risk. [48][49][50] …”
Section: Discussionmentioning
confidence: 99%
“…Improvement in health outcomes for the HIV-infected community through systematic attention to depression can also achieve one of the goals of the current United States HIV/AIDS strategy. 61 Although we could not determine whether depression was underdiagnosed in our population, we believe our findings provide further compelling evidence for ensuring that contemporary HIV-infected patients who are engaged in care are regularly screened for depression and treated, if indicated.…”
mentioning
confidence: 91%